METHOD OF DETERMINATION OF STATISTICAL CHARACTERISTICS FOR DIAGNOSTICS PROCESS EFFICIENCY FOR TELECOMMUNICATION AND RADIOELECTRONIC SYSTEMS - Solomentsev, Olexander; Zaliskyi, Maxim; Shcherbyna, Olga; Yashanov, Ivan (Science-based technologies, 2021)
The article concentrates on the issues of substantiation of statistical characteristics usage necessity for the efficiency index of diagnostics process for telecommunication and radioelectronic systems. It is known that utilization of telecommunication and radioelectronic systems for industrial use has a tendency to grow rapidly every year. Therefore, an inevitable requirement for these systems is to increase the level of reliability and maintainability. Ensuring the reliability and maintainability of telecommunication and radioelectronic systems is one of the main tasks of the operation system. The operation system includes equipment, personnel, documentation, resources, means of operation, control and measuring equipment. The operation system implements the processes of intended use, maintenance, repair, continuation of life service. Operational experience shows that current repairs consist of procedures for diagnostics, restoring serviceability and parameters monitoring. Analysis of the literature in the field of diagnostics of telecommunication and radioelectronic systems shows that insufficient attention is paid to the problem of determining the statistical characteristics of diagnostics efficiency indicators. However, most scientific results are related to the use of only mathematical expectations of efficiency indicators. Nevertheless, the efficiency indicator is a stochastic process, because the occurrence of failures is random. This process can be characterized by the distribution function, which contains complete information about it. The use of distribution function can make it possible to develop more accurate data processing algorithms in the operation systems for telecommunication and radioelectronic equipment. The probability of correct diagnostics is chosen as an indicator of the efficiency of the diagnostics process, because in the process of diagnostics errors of the first and second kind are possible. A step-by-step method for determining statistical characteristics has been developed for this efficiency indicator. As a result of its implementation, a probability mass function can be obtained for the probability of correct diagnostics. The methodology is explained by a specific example. The antenna system for radiomonitoring was chosen as the object of diagnostics. A diagnostic model and two variants of diagnostic programs based on the engineering method and the method of information parameter are built for it. As a result, two probability mass functions are calculated for the probability of correct diagnostics. Comparative analysis was also supplemented by the calculation of mathematical expectations and variances of the probability of correct diagnostics for different initial data. The results of the research can be used in the process of designing and improving the operation system for telecommunication and radioelectronic equipment during diagnostics process.